Udokan hearth of mineral resources: Factors shaping the quality of atmospheric air - Brychaeva, N.I. (E3S web of conferences, 2024)
The consequences of the impact of mining and ore processing industries on atmospheric air are acutely negative. Polluted atmospheric air entails a significant environmental risk to human health. The identification of factors that negatively affect the air quality of a mining enterprise and nearby territories actualizes the problem under consideration. The object of the study is the territory of the Udokan hearth of mineral resources. The subject of the study is the factors that shape the quality of atmospheric air. The purpose of the study is to analyze the negative effects of the main factors determining the ecological state of atmospheric air in the conditions of the Udokan hearth of mineral resources. The methodological basis of the research is the complex, structural, factual principles and approaches. The work uses general research methods (analysis, synthesis, generalization), as well as private scientific - factor analysis, which is understood as a method of complex and systematic study of the interaction of factors on the magnitude of performance indicators. The main factors shaping the ecological situation of the study area are identified: climatic, qualitative and quantitative indicators of polluting emissions. The necessity of constant monitoring of the state of the atmosphere for the development and implementation of a set of measures to reduce the negative impact of polluting emissions into the atmosphere is justified. Conclusions. The practical uniformity of the chemical composition of harmful emissions during the implementation of the main technological processes of mining and mining processing industries makes it possible to develop preventive measures to minimize the negative consequences of the development of mineral deposits in the mine atmospheric space.